Legal Protection of Customary Forests of the Awyu Tribe in South Papua From a National and International Law Perspective - Kristin, Nonce Kristin Gaman; Dwi Pratiwi Markus; Hadi Tuasikal (Jurnal Ius Constituendum, 2025)
Amid the expansion of extractive industries that threaten ecosystems and marginalize indigenous communities, the Awyu Tribe in South Papua faces increasing pressure over the ownership and protection of their customary forests. This study aims to explore the ownership conflict of Awyu customary forests, assess the effectiveness of national and international legal frameworks, and evaluate the implementation of state policies in securing indigenous rights and ecological justice. The urgency of this issue lies in the persistent neglect of the Awyu people's legal standing, where regulations often fail to reflect their lived realities and cultural values. Using a normative legal method, the research applies statutory, conceptual, comparative, and case-based approaches, relying on secondary data sourced from literature and analyzed through qualitative-descriptive techniques. Findings indicate that although both national and international law recognize indigenous rights, implementation on the ground is obstructed by bureaucratic inefficiencies and competing economic interests. The principle of Free, Prior, and Informed Consent (FPIC) is frequently disregarded, resulting in systemic land dispossession and environmental degradation. This research offers a novel perspective by integrating fragmented legal mechanisms into a cohesive approach to indigenous forest protection. As a normative recommendation, the study calls for stronger enforcement of FPIC, institutional reform to reduce regulatory bias, and the meaningful inclusion of indigenous voices in policy formulation and implementation.